2015
DOI: 10.3390/ijms16023188
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled Carbon Nanotubes Promote Cementoblast Differentiation and Mineralization through the TGF-β/Smad Signaling Pathway

Abstract: Excretion of cementum by cementoblasts on the root surface is a process indispensable for the formation of a functional periodontal ligament. This study investigated whether carboxyl group-functionalized multi-walled carbon nanotubes (MWCNT-COOH) could enhance differentiation and mineralization of mammalian cementoblasts (OCCM-30) and the possible signaling pathway involved in this process. Cementoblasts were incubated with various doses of MWCNT-COOH suspension. Cell viability was detected, and a scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Osteoblast differentiation is the key to bone formation, in which bone morphogenetic TGF-β/Smad signaling pathway is involved [40]. The previous studies revealed that Smad2/3 played an important role in the regulation of bone formation [41], and the expressions of Smad2/3 and p-Smad2/3 were elevated during cementoblast differentiation and mineralization [42]. Typically, the activation of the TGF-β/Smad signaling pathway mediates the phosphorylation of Smad2/3, which dimerizes with Smad4 and translocates to the nucleus, resulting in downstream gene transcription to direct cell differentiation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast differentiation is the key to bone formation, in which bone morphogenetic TGF-β/Smad signaling pathway is involved [40]. The previous studies revealed that Smad2/3 played an important role in the regulation of bone formation [41], and the expressions of Smad2/3 and p-Smad2/3 were elevated during cementoblast differentiation and mineralization [42]. Typically, the activation of the TGF-β/Smad signaling pathway mediates the phosphorylation of Smad2/3, which dimerizes with Smad4 and translocates to the nucleus, resulting in downstream gene transcription to direct cell differentiation [43].…”
Section: Discussionmentioning
confidence: 99%
“…They could create good conditions for the exchange of cell information and substance. 12 However, in the current literature, the effect of wound healing acceleration by electrospun nanofiber has only been examined at the pharmacodynamics stage. Therefore, the mechanisms of nanofiber-promoted wound healing remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…At different times, the staining of mineralized nodules was remarkably reduced in the miR-409-3p analog + DKK-1 group when compared with the miR-409-3p analog group ( Figure 5 C, P <0.01). At last, the protein expression of the key markers for osteoblast differentiation-related genes, including ALP, OCN, OPN, RUNX2 [ 22 ], were also found to be markedly up-regulated in miR-409-3p analog group and down-regulated after DKK-1 treatment ( Figure 5 D, P <0.05). Overall, inhibition of Wnt signaling by DKK-1 treatment blocked miR-409-3p induced enhancement of osteoblastic differentiation of MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…5C, p < 0.01). At last, the protein expression of the key markers for osteoblast differentiation-related genes, including ALP, OCN, OPN, RUNX2 [22], were also found to be markedly up-regulated in miR-409-3p analog group and down-regulation after DKK-1 treatment.…”
Section: Blocking Wnt/β-catenin Pathway Attenuates the Promotion Of Mmentioning
confidence: 96%